Religion in the social sciences: a socio-epistemological critique - Matthes, Joachim (Universiti Kebangsaan Malaysia, 2000)
In the effort to conceptualise social phenomena, social scientists are faced with the fundamental epistemological problem of having to translate cultural terms into scientific concepts, in the course of which the cultural contexts in which such terms are embedded are often neglected, or even systematically excluded. this can result in a 'loss of reality', and a corresponding danger of misinterpretation, in particular in cross-cultural and comparative studies. In this paper, this epistemological problem is discussed with respect to the concept of religion. For this purpose, the specific period of European cultural history in which this concept emerged, as well as the trajectories of its generalisation to a concept which appears to be universally applicable, is reconstructed and described. At the same time, an attempt is made to show how the original cultural meanings of the term have survived the efforts to generalise it, and how the concept of 'religion' as it is commonly used in the social sciences today still carries a hidden cultural load which could bias theory construction and empirical research. The paper argues for a methodology of 'heightened reflexivity' towards a cultural history of the core concepts which in the social sciences tend to be used in a definitory fashion.